Pembagian Harta Bersama Akibat Perceraian - Eko Sugianto; Wahyu Prawesthi; Siti Marwiyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Marriage is a sacred agreement in human life, although some marriages also fail and end in divorce. However, this divorce does not only stop at the end of the relationship between the two parties. But more than that, the problem of separation of joint property also often becomes a new problem after divorce. This study then aimed to review the implementation of divorce and division of property arising from marriage according to Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage. The research method used is normative, with a statutory approach and a conceptual approach. The results of the study showed that the legal basis for joint property is contained in Chapter VII Article 35 to Article 37 of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage. Based on this law, the path to division of joint property is divided through several mechanisms, namely based on religious law, based on customary law, and based on other laws. Compared to Law Number 1 of 1974, Law Number 16 of 2019 provides more detailed and modern regulations regarding joint property compared to previous provisions. Overall, according to Law Number 16 of 2019, the authority to settle the division of joint property arising from marriage involves the court in deciding fairly based on applicable law. The court has the responsibility to ensure that the division of property is carried out with the principle of justice, taking into account the contribution of each party and their needs and economic circumstances. In the case of mediation or agreements outside the court, the court still has the authority to assess and ensure that the decisions taken are in accordance with applicable legal provisions.